A new MWA limit on the 21 cm power spectrum at redshifts ∼13–17. Issue 4 (1st June 2021) - Yoshiura, S; Pindor, B; Line, J L B; Barry, N; Trott, C M; Beardsley, A; Bowman, J; Byrne, R; Chokshi, A; Hazelton, B J; Hasegawa, K; Howard, E; et al.
ABSTRACT: Observations in the lowest Murchison Widefield Array (MWA) band between 75 and 100 MHz have the potential to constrain the distribution of neutral hydrogen in the intergalactic medium at redshift ∼13–17. Using 15 h of MWA data, we analyse systematics in this band such as radio-frequency interference (RFI), ionospheric and wide field effects. By updating the position of point sources, we mitigate the direction-independent calibration error due to ionospheric offsets. Our calibration strategy is optimized for the lowest frequency bands by reducing the number of direction-dependent calibrators and taking into account radio sources within a wider field of view. We remove data polluted by systematics based on the RFI occupancy and ionospheric conditions, finally selecting 5.5 h of the cleanest data. Using these data, we obtain 2σ upper limits on the 21 cm power spectrum in the range of 0.1 h Mpc^-1k 1 h Mpc^-1 and at z = 14.2, 15.2, and 16.5, with the lowest limit being 6.3× 10^6 mK^2 at k=0.14 h Mpc^-1 and at z = 15.2 with a possibility of a few per cent of signal loss due to direction-independent calibration.